Virtual Objective Structured Clinical Examination Experiences and Performance in Physical Medicine and Rehabilitation Residency. (27th October 2022) - Kelly, Ryan; Leung, Gentson; Lindstrom, Heather; Wunder, Shane; Yu, Jaime C.
Abstract : Background: Virtual education has been described before and during the COVID-19 pandemic. Studies evaluating virtual objective structured clinical examinations with postgraduate learners are lacking. This study (1) evaluated the experiences of all participants in a virtual objective structured clinical examination and (2) assessed the validity and reliability of selected virtual objective structured clinical examination stations for skills in physical medicine and rehabilitation. Methods: Convergent mixed-methods design was used. Participants included three physical medicine and rehabilitation residency programs holding a joint virtual objective structured clinical examination. Analysis included descriptive statistics and thematic analysis. Performance of virtual to previous in-person objective structured clinical examination was compared using independent t tests. Results: Survey response rate was 85%. No participants had previous experience with virtual objective structured clinical examination. Participants found the virtual objective structured clinical examination to be acceptable (79.4%), believable (84.4%), and valuable for learning (93.9%). No significant differences between in-person and virtual objective structured clinical examination scores was found for three-fourth stations and improved scores in one fourth. Four themes were identified: (1) virtual objective structured clinical examinations are better for communication stations; (2) significant organization is required to run a virtual objective structured clinical examination; (3) adaptations are required compared with in-person objective structured clinical examinations; and (4) virtual objective structured clinical examinations provide improved accessibility and useful practice for virtual clinical encounters. Conclusions: Utility of virtual objective structured clinical examinations as a component of a program of assessment should be carefully considered and may provide valuable learning opportunities going forward.